The man in the white sharkskin suit my family's exodus from Old Cairo to the New World - Matalon Lagnado, Lucette (New York Ecco, 2007)
Lagnado re-creates the cosmopolitan glamour of Cairo in the years between World War II and Nasser's rise to power. Her father, Leon, was a boulevardier who conducted business in his signature white sharkskin suit on the elegant terrace of Shepheard's Hotel, and later, in the cozy, dark bar of the Nile Hilton. But with the fall of King Farouk, Leon and his family lose everything. As streets are renamed, neighborhoods of their fellow Jews disbanded, and the city purged of foreign influence, the Lagnados, too, must make their escape. With all of their belongings packed into 26 suitcases, their jewels and gold coins hidden in sealed tins of marmalade, Leon and his family depart for any land that will take them. The poverty and hardships they encounter in their flight from Cairo to Paris to New York are strikingly juxtaposed against the beauty and comforts of the lives they left behind.--From publisher description
Includes bibliographical references (p. [338]-340)
1
Keywords: Matalon Lagnado, Lucette; Jews -- Egypt -- Cairo -- Biography; Jews, Egyptian -- New York (State) -- Biography; Cairo (Egypt) -- Biography